2020
DOI: 10.1001/jamanetworkopen.2020.14475
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicare Mandatory Bundled Payment System for Hip and Knee Joint Replacement With Racial/Ethnic Difference in Joint Replacement Care

Abstract: This cohort study analyzes Medicare claims data to assess whether changes in joint replacement care are associated with Medicare’s Comprehensive Care for Joint Replacement (CJR) model among White, Black, and Hispanic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…41 The findings of this study represent relative improvements despite concerns that value-based payment models may exacerbate existing disparities. 41 Further timetrend patient demographic studies are needed to explore trends in socioeconomic status disparities in patients undergoing primary THA. This study is not without limitations.…”
Section: Demographicsmentioning
confidence: 76%
See 2 more Smart Citations
“…41 The findings of this study represent relative improvements despite concerns that value-based payment models may exacerbate existing disparities. 41 Further timetrend patient demographic studies are needed to explore trends in socioeconomic status disparities in patients undergoing primary THA. This study is not without limitations.…”
Section: Demographicsmentioning
confidence: 76%
“…41 In a retrospective cohort of Medicare claims from 2013 to 2017 among Caucasian, African American, and Hispanic patients undergoing TJA, Kim et al 41 found CJR was associated with decreased readmissions for African American patients with African American patients experiencing a greater decrease in discharges to post-acute facilities relative to Caucasian patients. 41 The findings of this study represent relative improvements despite concerns that value-based payment models may exacerbate existing disparities. 41 Further time-trend patient demographic studies are needed to explore trends in socioeconomic status disparities in patients undergoing primary THA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study included hospitals in 67 MSAs randomly selected by CMS to participate in the CJR model, along with hospitals from 103 control MSAs eligible for the model but not selected to participate. 7 Our study excluded joint replacement surgeries ineligible for CJR model participation (eg, people with Medicare as a secondary payer and hospitals in the Bundled Payments for Care Improvement initiative for joint replacement). We also excluded surgeries for patients with less than 12 months of enrollment prior to the surgery or less than 3 months following the surgery to ensure sufficient time to capture outcomes and health characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…We defined institutional postacute care services as any services provided in a skilled nursing facility, swing bed, inpatient rehabilitation facility, or long-term care hospital. 7 We adjusted spending for cost of living using the CMS wage index 8 and for inflation using the Consumer Price Index. 9…”
Section: Methodsmentioning
confidence: 99%